Organização do estágio por projetos de trabalho nos cursos de licenciatura do Instituto Federal do Amazonas-CMC - Souza, Heliamara Paixão de (2019)
This research emerged from the professional context of the author, who is a coordinator of Curricular Internship at the Amazonas Federal Institute - Campus Manaus Centro (CMC). The objective of the research was to understand how the Internship developed by Work Projects can contribute to the teaching and the teacher researcher training. Participated in the research, which occurred in two moments, students of the 7th period of the Biological Sciences degree course of the Amazonas Federal Institute - CMC. From the first moment, understanding what a Work Project is, twenty-one students participated; of these, three students participated in the second moment, construction of Work Projects in the Internship Schools. It is a qualitative research that used the collaborative research, structured in four phases: diagnosis, planning, implementation and evaluation. Regarding the techniques and instruments of the data collection, they were used, respectively, a focused interview and conversation wheel; audio recording and field diary. For the analysis it was necessary a detailed reading of the data collected, looking for answer to two central categories of the research, in view of its objective: the first, teaching learning; the second, the researcher teacher training. About the first category, the evidenced aspects were: a) knowledge articulation, in an interactive process of dialogue and exchange, conditions necessary for the knowledge construction about teaching, b) management of classroom activities, c) organization of teaching actions by the planning of activities, d) moments of reflection on the practices. Regarding to the second, it showed: a) articulation between theory and practice as part of a process that can’t be dissociated to produce knowledge, b) view that for the teacher, the classroom, is the research space, c) understanding that the investigative attitude is an essential component of the teacher's work. Because it is a research developed in a professional master's degree, an educational product is required. This one, created, developed and evaluated during the collaborative research done, is presented, in appendix, as "Proposal for the development of the Curricular Internship by Work Projects in the degree courses of the Amazonas Federal Institute - CMC".